2017
DOI: 10.1155/2017/6931497
|View full text |Cite
|
Sign up to set email alerts
|

Potential Challenges of Controlling Leishmaniasis in Sri Lanka at a Disease Outbreak

Abstract: The present works reviewed the existing information on leishmaniasis in Sri Lanka and in other countries, focusing on challenges of controlling leishmaniasis in the country, in an outbreak. Evidence from recent studies suggests that there is a possibility of a leishmaniasis outbreak in Sri Lanka in the near future. Difficulty of early diagnosis due to lack of awareness and unavailability or inadequacy of sensitive tests are two of the main challenges for effective case management. Furthermore, the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…Of these forms, the VL is considered to be the most virulent disease orientation. In Sri Lanka, CL is the predominant form of disease [ 6 ]. More than 2,000 cases have been identified from 2000 to 2009 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these forms, the VL is considered to be the most virulent disease orientation. In Sri Lanka, CL is the predominant form of disease [ 6 ]. More than 2,000 cases have been identified from 2000 to 2009 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 In relation to housing, mud or thatched walls, damp earthen floors and peridomestic vegetation each act to promote vector resting and breeding sites. 18 Longterm changes in meteorological conditions, notably global warming, have facilitated the incremental northward expansion of mosquito-borne tropical diseases such as dengue and malaria from more equatorial latitudes. 19 Environmental conditions including altitude, precipitation and humidity also influence the abundance of sandflies, 3 and there is justified concern that the distribution of phlebotomine vectors of Leishmania transmission may increase with climate change.…”
Section: Factors Affecting Disease Epidemiologymentioning
confidence: 99%
“…38 Nevertheless, the exact number of species that are capable of transmitting leishmaniasis in Sri Lanka is still not known, while the possibility of disease transmission by other potential vectors such as biting midges is yet to be established. 18 In a detailed nationwide entomological trapping study, the highest number of sandflies collected was from the south-west coastal area of Kathaluwa, located in the Galle District. 39 This is part of the Southern Province, which experiences a hot and humid tropical rainforest climate.…”
Section: Disease Emergence and Prevalence In Sri Lankamentioning
confidence: 99%
See 1 more Smart Citation
“…Although a total of 20 species have been recorded in Sri Lanka, the only confirmed vector for disease transmission is Phlebotomus argentipes, which has been reported from almost all the endemic regions for the disease [3][4][5][6][7][8][9]. Many studies have reported that this species is the main vector for visceral leishmaniasis (VL) caused by Leishmania donovani in Indian subcontinent [10][11][12].…”
Section: Introductionmentioning
confidence: 99%